Efektivitas model pembelajaran blended learning berbantuan vaksin terhadap hasil belajar mahasiswa pada mata kuliah geometri - Suriyah, Puput; Utami, Anita Dewi; Hasanudin, Cahyo (Jurnal Math Educator Nusantara: Wahana Publikasi Karya Tulis Ilmiah di Bidang Pendidikan Matematika, 2022)
The purpose of this study was to prove whether the blended learning model assisted by VAKSIN (Video Animasi untuk Sistem Pembelajaran Online/Video Animation for Online Learning Systems) is more effective than the online learning model on student learning outcomes in the fourth semester of the Mathematics Education Study Program. The posttest only control design was carried out in the Geometry course at IKIP PGRI Bojonegoro for the 2021/2022 academic year. This study used a saturated sampling technique where all members of the population are used as samples. Data collection techniques in this study used documentation and test techniques. Test the hypothesis used t-test. The results of data analysis obtained by testing the hypothesis in the experimental class and control obtained tcount= 3,18219098 dengan ttable = 1,99084707. Karena tcount > ttable hence H0 is rejected so it can be concluded that the learning outcomes of the fourth semester students of the Mathematics Education Study Program of IKIP PGRI Bojonegoro who were subjected to VAKSIN-assisted blended learning were more effective than those who were subjected to online learning.